Mesozoic Coleopteran Faunas fromArgentina: Geological Context, Diversity, Taphonomic Observations, and Comparison with Other Fossil Insect Records - Lara, Maria Belén (2012)
The order Coleoptera is the most diversified group of the Class Insecta and is the largest group of the Animal Kingdom. This contribution reviews the Mesozoic insects and especially the coleopteran records from Argentina, based on bibliographical and unpublished materials (86 described species, 526 collected specimens). The material came from different geological units from the late Middle Triassic to the Late Triassic (Bermejo, Cuyo, and Malargüe basins) to the Middle-Late Jurassic and Early Cretaceous (Deseado Massif, Cañadón Asfalto, and San Luis Basin). The coleopteran record is composed of 29 described species with 262 collected specimens (isolated elytra) mainly represented by Triassic species and only four specimens recorded in Jurassic units, all of them currently unpublished. These fossil coleopterans provide fundamental information about the evolution of insects in the Southern Hemisphere and confirm the Triassic Argentinean insect deposits to be among the most important in the world.